Exposure Doses to Technologists Working in 7 PET/CT Departments - Weiguo Li; Lianying Fang; Jieqing Li (SAGE Publishing, 2020)
Objective: The aim of this study was to measure occupational exposure doses of technologists who dispense and inject radiopharmaceuticals in 7 positron emission tomography/computed tomography (PET/CT) departments. This was done with the goal to help improving protective designs in PET departments and/or establishing national protection standards. Method: Common LiF thermoluminescence dosimeters (TLDs) were placed on the chest and necklace of the technologists to monitor whole-body and thyroid doses, respectively. Ring TLDs were also worn on both index fingers to measure individual hand doses. All TLDs were assembled and measured once every 3 months for a total of 12 months. Additionally, we measured and compared the dose of TLDs attached to both the inside and the outside of the technologist's lead coat. Results: Technologists received relatively high exposures, which accounted for 64% to 94% of the collective dose in their respective departments. Their thyroid doses ranged from 1.2 to 1.7 mSv/a; some technologists' hand doses exceeded 500 mSv/a. Use of a lead coat reduced the average dose by 8%. Conclusion: Technologists working in PET/CT departments were the main population exposed to radiation. This work underscores the need for enhanced protective measures for these workers to better reduce their exposure, particularly for their hands.